Penerapan Sasaran Keselamatan Pasien melalui Penilaian Resiko Jatuh yang Terintegrasi dengan Rekam Medik Elektronik - Djarang, Lilyance; Hariyati, Rr Tutik Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to discuss the methods used to implement patient safety standards by assessing the fall risk in hospitals integrated with electronic medical records obtained from several research journals. The technique used is a literature review from journal searches in online databases, including Pubmed, ProQuest, Clinical Key Nursing, and Science. The research results show that using technology to prevent patient falls generally indicates positive results, which are very beneficial for patients and improve the quality of patient safety in hospitals. In conclusion, ways to prevent falls in hospital patients need to be further developed so that they can show better results. Keywords: Assessment, Patient Safety, Nursing, Electronic Medical Records, Fall Risk